Explaining age differences in positive attitudes towards national commemorations: The role of what people commemorate - de Regt, Sabrina; Jaspers, Eva; van der Lippe, Tanja (Wiley-Blackwell Publishing Ltd, 2017)
Commemorations of shared national history are important to the process of nation-building. Support for such national commemorations is not, however, evenly distributed in societies. Because this could endanger the possible integrative function of commemorative ceremonies, it is important to understand the sources of structural differences in support. In this article, age differences in support for national commemorations in the Netherlands are examined. It is argued that because age cohorts grow up with different ideas on what should be commemorated they also differ in value attached to such commemorations. Data from the National Freedom Enquiry 2012 show that older persons more often associate national commemorations with the Second World War than younger persons do, and that this is the reason why they are more supportive of the annual celebration of Liberation Day. In the concluding section, it is argued that more (quantitative) studies should be conducted in order to truly understand the mechanisms behind support of national commemorations as this may help us to better comprehend the processes construing feelings of national belonging.
Keywords: Age cohorts; Cultural trauma; Mediation analysis; Support national commemorations; Taverne; Geography, Planning and Development; Arts and Humanities (miscellaneous); Political Science and International Relations